2017
DOI: 10.1016/j.jpeds.2017.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Shared Reading Quality and Brain Activation during Story Listening in Preschool-Age Children

Abstract: Objective To explore the relationship between maternal shared reading quality (verbal interactivity and engagement) and brain function during story listening in at-risk, preschool-age children, in the context of behavioral evidence and American Academy of Pediatrics recommendations. Study design In this cross-sectional study, 22 healthy, 4-year-old girls from low-socioeconomic status (SES) households completed functional MRI using an established story listening task, followed by videotaped observation of un-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 73 publications
3
65
0
5
Order By: Relevance
“…These components of "dialogic reading" (Whitehurst et al, 1988) were related to differences in brain activation in Broca's area. Thus, Romeo et al (2018), Hutton et al (2017), and numerous behavioral studies (e.g., Cartmill et al, 2013;Malin et al, 2014) find that language quality and reading quality are contributors to children's brain development and language growth. In this regard, SSM report on the extensive personal stories told in working-class African American families to their children, certainly valuable exchanges for children's later vocabulary development (Sperry & Sperry, 1996, 2000.…”
Section: Quantity Versus Quality Of Communicativementioning
confidence: 99%
“…These components of "dialogic reading" (Whitehurst et al, 1988) were related to differences in brain activation in Broca's area. Thus, Romeo et al (2018), Hutton et al (2017), and numerous behavioral studies (e.g., Cartmill et al, 2013;Malin et al, 2014) find that language quality and reading quality are contributors to children's brain development and language growth. In this regard, SSM report on the extensive personal stories told in working-class African American families to their children, certainly valuable exchanges for children's later vocabulary development (Sperry & Sperry, 1996, 2000.…”
Section: Quantity Versus Quality Of Communicativementioning
confidence: 99%
“…Interestingly, stories stimulation driven by adults feeds into executive functions brain networks even in preschool‐age children . The level of dialogue with mothers was also related to brain regions related to language, socio‐emotional and executive functions in preschoolers . Posner and Petersen suggested that the mentioned cognitive abilities are an ‘attentional network’ that can be divided into two subcomponents or systems .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated increased activation and functional connectivity in children who are more deeply engaged during shared reading in 22 motherdaughter pairs [71]. The same group also associated shared reading quality scores with brain activation, and they found a positive correlation between shared reading quality scores with activation in left-hemispheric regions supporting expressive and complex language, social-emotional integration, and working memory in 22 healthy, 4-year-old girls from low SES [72]. Their findings suggest that the use of shared parent-child reading is crucial for emergent reading experience, but the quality of this experience has also a strong impact on brain development.…”
Section: Brain Imaging Evidencementioning
confidence: 90%